2010
DOI: 10.1177/0047287510379163
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Model of Durkheim’s Theory of Emotional Solidarity among Residents of a Tourism Community

Abstract: The purpose of this study was to test the theoretical framework of emotional solidarity in seeking to better explain the dynamic, complex relationships existing between residents and tourists. Measurement and structural models pertaining to the framework were simultaneously estimated, both of which were deemed to have good model fit based on incremental and absolute model fit indices. Three antecedent constructs (i.e., shared beliefs, shared behavior, and interaction) were all found to be significant predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
143
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(163 citation statements)
references
References 58 publications
(93 reference statements)
10
143
5
1
Order By: Relevance
“…The study supports past findings that shared beliefs, shared behaviors, and interactions between residents and tourists promote mutual understanding, respect, and welcoming attitudes among residents and tourists [10,16,17]. Further, the study also supports the earlier study outcomes that for a destination to be ethical and filled with ethic of care to its people and places, local tourism stakeholders, and incoming tourists are required to create an endearing environment that ensures justice, fairness, equality, respect to diversity, and concern for others [5,8,[34][35][36].…”
Section: Theoretical Implicationssupporting
confidence: 89%
See 1 more Smart Citation
“…The study supports past findings that shared beliefs, shared behaviors, and interactions between residents and tourists promote mutual understanding, respect, and welcoming attitudes among residents and tourists [10,16,17]. Further, the study also supports the earlier study outcomes that for a destination to be ethical and filled with ethic of care to its people and places, local tourism stakeholders, and incoming tourists are required to create an endearing environment that ensures justice, fairness, equality, respect to diversity, and concern for others [5,8,[34][35][36].…”
Section: Theoretical Implicationssupporting
confidence: 89%
“…Others have defined such interactions by financial exchanges applying theories, such as social exchange theory [14,15]. However, in recent years, research works undertaken by Woosnam and colleagues [10,16,17] have established that tourist-host interactions can be analyzed beyond relations of reciprocity and financial transactions.…”
Section: Emotional Solidaritymentioning
confidence: 99%
“…The result that welcome tourists behaviour affected attitude toward tourism and pro-tourism behaviour supported the findings of the studies by Woosnam (2011) and Woosnam and Aleshinloye (2013). Similarly, in keeping with the findings of Stylidis and Terzidou (2014), Gursoy, Chi, and Dyer (2010), and Dyer, Gursoy, Sharma, and Carter (2007), the present study revealed that perceived local economy affected both attitude toward tourism and pro-tourism behaviour.…”
supporting
confidence: 90%
“…The scale consists of three factors; sympathetic understanding, welcoming visitors, and emotional closeness. However, many researches such as Woosnam (2011), and Woosnam and Aleshinloye (2013) used only welcoming visitors as a factor to measure emotional solidarity scale.…”
Section: Pro-tourism Behaviour and Attitude Toward Tourismmentioning
confidence: 99%
“…In addition to the ESS being utilized in work to support Durkheim's initial framework, where the construct was significantly predicted from residents' interaction, shared beliefs, and shared behavior with tourists (Woosnam 2011a;Woosnam 2011b), the construct (and its corresponding dimensions) has been considered an outcome of length of residence (Woosnam et al 2014). Woosnam and Aleshinloye (2013), in building on the work of Woosnam (2012), tested Durkheim's model from a tourists' perspective, showed how interaction, shared beliefs, and shared behavior each significantly predicted levels of emotional solidarity.…”
Section: Emotional Solidaritymentioning
confidence: 99%